From entry to finals: progression and variability of swimming performance at the 2022 FINA World Championships - Santos, C. C.; Fernandes, R. J.; Marinho, D. A.; Costa, M. J. (Journal of Sports Science & Medicine, 2023)
The aim of the present study was two-fold: (i) to analyze the progression and variability of swimming performance (from entry times to best performances) in the 50, 100, and 200 m at the most recent FINA World Championships and (ii) to compare the performance of the Top16, semifinalists, and finalists between all rounds. Swimmers who qualified with the FINA A and B standards for the Budapest 2022 World Championships were considered. A total of 1102 individual performances swimmers were analyzed in freestyle, backstroke, breaststroke, and butterfly events. The data was retrieved from the official open-access websites of OMEGA and FINA. Wilcoxon test was used to compare swimmers` entry times and best performances. Repeated measures ANOVA followed by the Bonferroni post-hoc test were performed to analyze the round-to-round progression. The percentage of improvement and variation in the swimmers` performance was computed between rounds. A negative progression (entry times better than best performance) and a high variability (> 0.69%) were found for most events. The finalists showed a positive progression with a greater improvement (~1%) from the heats to the semifinals. However, the performance progression remained unchanged between the semifinals and finals. The variability tended to decrease between rounds making each round more homogeneous. Coaches and swimmers can use these indicators to prepare a race strategy between rounds.